OPTIMIZATION OF CORN DRYING METHODS: A COMPARATIVE STUDY OF TRADITIONAL VARIETIES AND MODERN HYBRIDS - Matin, Ana; Brandić, Ivan; Jurišić, Vanja; Tomić, Ivana; Matin, Božidar; Krička, Tajana; Mateja, Grubor; Pucko, Filip; Jovičić, Nives; Špelić, Karlo (Journal on Processing and Energy in Agriculture, 2025)
Understanding the effects of different drying methods on different corn varieties, both before and after drying, is crucial for selecting the most suitable hybrids and optimizing drying techniques. In this study, traditional white and red corn varieties and modern hybrid were investigated and the efficiency of vacuum drying and fluidized bed drying at temperatures of 70°C, 80°C and 90°C were compared. The results show that vacuum drying is generally more effective in maintaining quality, while fluidized bed drying offers a significantly faster drying rate. Hybrid corn showed the fastest moisture loss, while traditional varieties showed greater resistance to drying. These results provide valuable insights into the most suitable drying conditions for the different corn varieties, which ultimately improve product quality and overall processing efficiency. Future research should investigate additional technological factors such as energy consumption, drying uniformity and effects on nutrient composition to further refine drying methods for commercial application.